A Low Tumor Mutational Burden and PTEN Mutations Are Predictors of a Negative Response to PD-1 Blockade in MSI-H/dMMR Gastrointestinal Tumors - Chida, Keigo; Kawazoe, Akihito; Kawazu, Masahito; Suzuki, Toshihiro; Nakamura, Yoshiaki; Nakatsura, Tetsuya; Kuwata, Takeshi; Ueno, Toshihide; Kuboki, Yasutoshi; Kotani, Daisuke; Kojima, Takashi; Taniguchi, Hiroya; et al. (Clinical cancer research, 2021)
This study performed a comprehensive molecular characterization of microsatellite instability-high (MSI-H)/mismatch repair-deficient (dMMR) gastrointestinal (GI) tumors to elucidate predictors of response to PD-1 blockade. Forty-five patients with MSI-H/dMMR GI tumors, including gastric cancer, colorectal cancer, cholangiocarcinoma, small intestine cancer, pancreatic cancer, and duodenal cancer, receiving PD-1 blockade were analyzed. We conducted the genomic profiling of GI tumors by whole-exome sequencing or targeted next-generation sequencing. The tumor microenvironment was evaluated by transcriptomic analysis and multiplex fluorescence IHC. Patients with low tumor mutational burdens (TMBs) had lower objective response rates (ORRs; 0% vs. 48.8%) and a significantly shorter progression-free survival (PFS; 2.3 vs. 15.6 months; HR, 6.20; = 0.002) than those with high TMBs. Among common gene alterations in GI tumors, only mutations, which were mutually exclusive with a low TMB, were significantly associated with a lower ORRs than wild-type (21.4 vs. 54.8%; odds, 4.45; = 0.045). Compared with wild-type mutations in the phosphatase domain were associated with significantly lower ORRs (12.5 vs. 54.8%; = 0.049), shorter PFS (2.6 vs. 15.6 months; HR, 5.04; < 0.001), lower intratumoral CD8 T-cell levels, higher intratumoral CD204 macrophage levels, and PI3K/AKT/mTOR pathway enrichment, whereas mutations in the C2 domain were not. Low TMBs and mutations, especially mutations in the phosphatase domain associated with an immunosuppressive environment, were mutually exclusive and might be negative predictors of PD-1 blockade responses in patients with MSI-H/dMMR GI tumors.